2021
DOI: 10.1016/j.jsams.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards more valid simulations of slopestyle and big air jumps: Aerodynamics during in-run and flight phase

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These studies seek to inform jump construction and course design—and hence athlete safety—through the collection and use of new data. Wolfsperger et al documented the air drag and lift during the in-run and flight phase of ski and snowboard slopestyle and big air, across various disciplines, postures and apparel 29. They also combined, for the first time, kinematic athlete data and comprehensive snow-surface measurements to infer the coefficient of friction of freestyle skis and snowboards across a wide range of snow conditions, from very fast to very slow snow conditions 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies seek to inform jump construction and course design—and hence athlete safety—through the collection and use of new data. Wolfsperger et al documented the air drag and lift during the in-run and flight phase of ski and snowboard slopestyle and big air, across various disciplines, postures and apparel 29. They also combined, for the first time, kinematic athlete data and comprehensive snow-surface measurements to infer the coefficient of friction of freestyle skis and snowboards across a wide range of snow conditions, from very fast to very slow snow conditions 30.…”
Section: Discussionmentioning
confidence: 99%
“…Wolfsperger et al documented the air drag and lift during the in-run and flight phase of ski and snowboard slopestyle and big air, across various disciplines, postures and apparel. 29 They also combined, for the first time, kinematic athlete data and comprehensive snow-surface measurements to infer the coefficient of friction of freestyle skis and snowboards across a wide range of snow conditions, from very fast to very slow snow conditions. 30 Both the air drag and the ski/snowboard friction have direct influence on the athlete's take-off speed and therefore landing impact, and, hence, ultimately their injury risk.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Athletes wore the same, regular-fit personal ski or snowboard apparel for each test day (Figure 2). For the athletes taking part in this study aerodynamic drag areas were quantified in a wind tunnel experiment using the same posture and apparel as during the gliding tests (Wolfsperger et al, 2021). Athletes' kinematics, wind velocity, meteorological parameter, and snow parameters were captured as described below.…”
Section: Test Designmentioning
confidence: 99%
“…The relative airflow velocity (v rel ) resulted from the sum of wind and athlete velocity. Speed dependent drag and lift area (c D A, c L A) were determined by wind tunnel measurements for each athlete considering their personal apparel and posture characteristics (Wolfsperger et al, 2021). This allowed an accurate calculation of the aerodynamic force components of drag and lift throughout each run (Eq.…”
Section: Kinematicsmentioning
confidence: 99%
“…In order to evaluate the influence of the field wind environment on cross-country skiing athletes' performance, the first step is to obtain the wind-induced aerodynamic drag of the athletes in the ski field wind environment. In recent years, many researchers have carried out research work on the acquisition of athletes' wind-induced aerodynamic drag through numerical calculation methods based on computational fluid dynamics (CFD) and wind tunnel experiments [6][7][8][9]. Chen [10] used steady and unsteady models to simulate 2D athlete models, and the results indicated that wind and posture affect the aerodynamic performance of a skier during the flight stage.…”
Section: Introductionmentioning
confidence: 99%